Retrospective Comparison Between International Consensus Diagnostic Criteria (ICDC) Without Using Histological Information and the Histological Diagnosis in Surgical Patients with Focal Autoimmune Pancreatitis - Ikeura, Tsukasa; Detlefsen, Sönke; Zamboni, Giuseppe; Amodio, Antonio; Vitali, Francesco; Gabbrielli, Armando; Benini, Luigi; Klöppel, Günter; Okazaki, Kazuichi; Vantini, Italo; et al. (JOP. Journal of the Pancreas, 2013)
Context International consensus diagnostic criteria (ICDC) for autoimmune pancreatitis (AIP) have been proposed to diagnose type 1 AIP, type 2 AIP and AIP not-otherwise specified (AIP-NOS). Objective The aim of this international multicenter study was to evaluate the possibility of correctly diagnosing AIP itself and its subtype by ICDC in focal AIP patients. Methods Thirty patients (type 1 AIP in 23 and type 2 AIP in 7) diagnosed as AIP based on histology of surgical specimens were classified according to ICDC based on their preoperative data. Results Pancreatic core biopsies and diagnostic steroid trial were not preoperatively performed in any of the patients. Based on preoperative data, ICDC diagnosed 6 patients (20%) as type 1 AIP and 24 (80%) as probable AIP. Assuming all patients had responded to a steroid trial preoperatively, ICDC would have diagnosed 8 patients (27%) as type 1 AIP, 4 (13%) as type 2 AIP, 10 as AIP-not otherwise specified (33%) and 8 (27%) as probable AIP. In the hypothetical situation, 7 of 8 type 1 AIP patients and 3 of 3 type 2 AIP patients would have been classified into the correct subtype of AIP. Conclusion In this retrospective study, the accuracy of ICDC without preoperative histology was quite low. A steroid trial enhances the possibility of correctly diagnosing AIP by ICDC despite of the lack of histology. However, some patients cannot be diagnosed as having AIP or be classified into the correct subtype without histology.